Blog Academic Assisted Inquiry Strategy for Conceptual Understanding of Physics Learning through 21st Century Learning Attitudes - Ira Nofita Sari; Lia Angraeni; Nurussaniah (Postgraduate, University of Mataram, 2023)
This research aims to determine the impact of learning using inquiry strategies assisted by academic blogs on the 21st century skills of students in the Physics Education Study Program at IKIP PGRI Pontianak. This research is a pre-experimental design research with a One group pretest-posttest design. The sample used was all 18 fifth semester students. The data collection technique is to determine conceptual abilities using tests, while to determine 21st century skills, namely 4C skills (Critical Thinking, Communication, Collaboration and Creativity) using observation techniques. The data collection tools used were test questions and observation sheets. Based on data analysis, it is known that there is a significant increase in students' understanding of concepts before and after learning in the high category. Students master 21st century skills, namely critical thinking, communication, collaboration, and creativity in the high category in every lesson. The academic blog-based inquiry learning model is innovative in improving the quality of physics learning in the 21st century educational era.